In situ preparation of MgCo2O4 nanosheets on Ni-foam as a binder-free electrode for high performance hybrid supercapacitors. Issue 19 (30th April 2018) - Vijayakumar, Subbukalai; Nagamuthu, Sadayappan; Ryu, Kwang-Sun
Abstract : MgCo2 O4 nanosheets grown on Ni-foam exhibited a maximum specific capacity of 947 C g −1 at 2 A g −1 . Abstract : A binder-free, MgCo2 O4 nanosheet-like architecture was prepared on Ni-foam using a hydrothermal method. MgCo2 O4 /Ni-foam was characterized by X-ray diffraction, field emission scanning electron microscopy (FESEM), and transmission electron microscopy techniques. The FESEM image revealed a nanosheet array-like architecture. The MgCo2 O4 nanosheets grown on Ni-foam exhibited the maximum specific capacity of 947 C g −1 at a specific current of 2 A g −1 . Approximately 96% of the specific capacity was retained from the maximum specific capacity after 5000 continuous charge–discharge cycles. This hybrid device exhibited a maximum specific capacity of 52 C g −1 at a specific current of 0.5 A g −1, and also exhibited a maximum specific energy of 12.99 W h kg −1 at a specific power of 448.7 W kg −1 . These results confirmed that the binder-free MgCo2 O4 nanosheets grown on Ni-foam are a suitable positive electrode material for hybrid supercapacitors.